Seroprevalensi Toxoplasma gondii pada Kambing dan Bioassay Patogenitasnya pada Kucing - Dewi, Ni Made Yunik Novita Dewi; Damriyasa, I Made Damriyasa; Suratma, Nyoman Adi (Veterinary Science and Medicine Journal; Vol 1 No 2 (2013), 2013)
Normal 0 false false false EN-US X-NONE X-NONE The study aimed to determine seroprevalence of Toxoplasmosis in goats sloughtered at Kampung Jawa, Denpasar, Bali and to evaluate their pathogenicities through bioassay in cats.One hundred serums and meats of goats were collected. Anti- Toxoplasma gondii antibody was determined using Indirect Haemaglutination (IHA) test. The p athogenicity bioassay of Toxoplasma gondii was carried out through inoculating the meats of goats which had seropositive of Toxoplasma gondii to the cats. The pathogenicity was evaluated using the intensity of oocyte sheding from the cats. The result showed that the seroprevalence of Toxoplasmosis was 46%. There was not significant difference between pathogenicity of Toxoplasma gondii in cat inoculated with meat of goat which had a high and low titer of antibody against Toxoplasma gondii. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; text-align:justify; line-height:150%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin;}
Keywords: Toxoplasma gondii, seroprevalence, pathonegicity, goat, cat